Analisis Fenomena Inner Child Dan Self-Reward dalam Perspektif Ekonomi Syariah - Muchtar, Evan Hamzah (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
Abstract The phenomenon of self-reward and inner-child-based healing is increasingly popular among Millennials and Gen Z, particularly through social media narratives that emphasize the right to happiness and emotional recovery. This article aims to examine the meaning of emotional consumption in self-reward practices from the perspective of Islamic economics. Using a phenomenological qualitative approach, data were collected through non-participant observation of narrative content on digital platforms. The analysis reveals that self-reward consumption can function as a means of healing, yet it risks deviation if not grounded in the values of maslahah, tazkiyah, and spiritual self-regulation. Therefore, healing-oriented consumption should be directed not merely toward emotional gratification, but as part of a spiritual journey toward barakah and a balanced life.. Keywords: Inner child, Self-reward, Syariah economic perspective